TINJAUAN YURIDIS TINDAK PIDANA PENYALAHGUNA NARKOTIKA GOLONGAN I BUKAN TANAMAN BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA (STUDI PUTUSAN NOMOR 621/PID.SUS/2020/PN.JKT.BRT): Indonesia - Syafrudin Wijaya; Elfrida R. Gultom (UNES Law Review, 2023)
Drug abusers should get rehabilitation punishment because rehabilitation is an alternative form therefore abusers are guaranteed by the narcotics law to get rehabilitation sentences instead of imprisonment, Such as the case of Buchari Hy Bin Hamdan Yahya, legally proven and convinced guilty of committing the crime of "Class I Non-Plant Narcotics Abusers" which ended in a prison sentence. The subject matter raised is Analysis Does the Defendant Fulfill the Elements of Article 112 Paragraph (1) and/or 127 Paragraph (1)?, (Study of Decision Number 621/Pid.Sus/2020/PN.Jkt.Brt) and Analysis What Are the Types of Punishment for Drug Abusers? (Study of Decision Number 621/Pid.sus/2020/PN.Jkt.Brt). This research uses a type of normative legal research that is descriptive analytical, using secondary data obtained from literature studies and also primary data obtained by interviews, and data processed qualitatively by drawing deductive logic conclusions. The conclusion of the study is (1) The defendant with Article 112 paragraph (1) seems similar to the article of abuser, but this article is contrary to the purpose of Law Number 35 of 2009 concerning Narcotics article 4d where the abuser is guaranteed to get rehabilitation efforts but with article 112 paragraph (1) this abuser is justri imprisoned, if viewed from article 127 paragraph (1) point a the defendant who is sentenced to 2 years 6 months in prison should be a judge can decide to pay attention to article 127 paragraph (2) of Law Number 35 of 2009 concerning Narcotics, "In deciding the case of the judge as referred to in paragraph (1) of Law Number 35 of 2009 concerning Narcotics, the judge is given the authority to decide the defendant to undergo treatment through medical rehabilitation and social rehabilitation, both guilty and innocent. (2) Abusers shall be punished in the form of rehabilitation instead of imprisonment, because rehabilitation is an alternative form of punishment Abusers are guaranteed by the Narcotics Law to be rehabilitated and judges must consider the condition of the level of drug dependence (Article 55 of Law Number 35 of 2009 concerning narcotics), and pay attention to the authority of Article 103 regulated in the Narcotics Law.